Funding for MSMEs Selling Seaweed on Export Destination Coast - Murdiono, Jatmiko; Winarsih, Sri; Louise Panggabean, Helena; Sani, Indra (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The aim of this study is to provide a better understanding of the challenges and opportunities in supporting MSMEs in the seaweed sector, as well as formulate concrete measures to improve their access to funding necessary for the growth and sustainability of their businesses. This research utilizes a qualitative approach. Qualitative research methodology is a set of techniques and procedures used to collect, analyze, and interpret data in qualitative research studies. This approach aims to understand social phenomena in depth, focusing on collecting rich and detailed data through non-numerical methods such as interviews, observations, and focus groups. Qualitative research methodology is a flexible and adaptable approach, allowing researchers to explore in depth complex social phenomena. Various methods were used to collect, analyze, and interpret data, which proved invaluable in understanding the experiences, views, and meanings possessed by participants in research studies. In the context of this study, data collection was carried out through a literature survey. Seaweed has been widely used by humans and various industries, providing an impact on the community that plants and preserves. As an economic source for the community, it also helps preserve the sea with seaweed as an economic source. Identify financing challenges, strategies to improve access to financing, collaboration among stakeholders, and examples of successful case studies. With a good understanding of these issues, solutions can be formulated to support the growth and sustainability of MMeS in the seaweed industry. In various countries around the world, especially in ASEAN, MMeS has been running by dabbling in seaweed conservation with various dynamics and helping ecosystems in the sea as well as a source of life for the community. Recommendations on the role of local or local governments to assist funding, exports, and the need for assistance, besides that the contribution of the results of this research is only a small part in qualitative form in participation in collaboration.